THE EFFECT OF RETURN ON ASSETS (ROA), DEBT TO ASSETS (DAR), EARNINGS PER SHARE (EPS), GROWTH, AND SIZE ON COMPANY VALUE IN MANUFACTURING COMPANIES - Gracia Oktaviane Lungkang; Fransisca Hanita Rusgowanto (Applied Accounting and Management Review (AAMAR), 2022)
This study aims to obtain empirical evidence of the effect of return on assets, debt to assets, earnings per share, growth and size on firm value. This study uses quantitative secondary data with purposive sampling method and multiple linear regression analysis, the total sample in this study is 30 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The results of this study indicate that return on assets and debt to assets have a significant effect on firm value. Meanwhile, earnings per share, growth and size have no significant effect on firm value.